2014
DOI: 10.1371/journal.pone.0113090
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Ancestral and Functionally Relevant CD5 Variants in Systemic Lupus Erythematosus Patients

Abstract: ObjectiveCD5 plays a crucial role in autoimmunity and is a well-established genetic risk factor of developing RA. Recently, evidence of positive selection has been provided for the CD5 Pro224-Val471 haplotype in East Asian populations. The aim of the present work was to further analyze the functional relevance of non-synonymous CD5 polymorphisms conforming the ancestral and the newly derived haplotypes (Pro224-Ala471 and Pro224-Val471, respectively) as well as to investigate the potential role of CD5 on the de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 16 publications
(28 citation statements)
references
References 47 publications
(57 reference statements)
2
26
0
Order By: Relevance
“…The second study evaluated two cohorts of melanoma patients and again showed a higher survival rate in those carrying the ancestral haplotype in homozygosis [68]. These findings were in agreement with previous work [69] reporting that the ancestral A471 variant translated into a lymphocyte hyper-responsiveness after TCR/CD3 crosslinking, reflected by higher thymidine incorporation and IL-2 and IFNγ release. This phenotype led to a worse autoimmune prognosis.…”
Section: Cd5 In Cancer Immunotherapysupporting
confidence: 86%
“…The second study evaluated two cohorts of melanoma patients and again showed a higher survival rate in those carrying the ancestral haplotype in homozygosis [68]. These findings were in agreement with previous work [69] reporting that the ancestral A471 variant translated into a lymphocyte hyper-responsiveness after TCR/CD3 crosslinking, reflected by higher thymidine incorporation and IL-2 and IFNγ release. This phenotype led to a worse autoimmune prognosis.…”
Section: Cd5 In Cancer Immunotherapysupporting
confidence: 86%
“…Although little is known about the role of this SNP in CD5‐mediated functions, recent data have shown that B‐CLL patients that bare an ancestral haplotype with a proline instead of a leucine at position 224 (P224L) and an alanine instead of a valine at position 471 (A471V) present better prognosis and longer lifespan, and the same has been reported in melanoma patients . In this context, this SNP also appears to be biologically relevant in T cells, as suggested by a recent report showing that T lymphocytes carrying the ancestral 471 alanine have an enhanced proliferation and produce increased levels of IL‐2 and IFN‐γ when stimulated with anti‐CD3 antibodies …”
Section: Role Of Cd5 In B Cell Immunobiologymentioning
confidence: 86%
“…The rs2229177 variants together with another frequent SNP coding for a Pro to Leu substitution at the extracellular region of CD5 (rs2241002, NM_014207.3:c.671C > T, p.Pro224Leu) constitute different haplotypes, one of which (Pro224‐Val471) has been positively selected in East Asian populations . Functional analyses reveal that homozygous carriers of the ancestral Pro224‐Ala471 (CC) haplotype present higher in vitro T cell proliferative responses and a more severe clinical form of Systemic Lupus Erythematosus compared to homozygous individuals for the more recently derived Pro224‐Val471 (CT) haplotype . This finding suggests a link between differential regulation of T‐cell signaling by CD5 variants and distinct autoimmune disease outcome.…”
mentioning
confidence: 99%